Overview Of Safety Equipment Above KMP. Satria Pratama At The Kuala Tungkal – Telaga Punggur France Track - Slamet Prasetyo Sutrisno; Ferdinand Pusriansyah; Ella Jelita Siringoringo (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
Kuala Tungkal Ferry Port is a port managed by BPTD Region V Jambi. Kuala Tungkal Ferry Port serves 2 routes with 2 Ro-Ro ships . One of the important components in ferry transportation is safety. Safety is addressed not only to service users but also to crew members. On ships operating at the Kuala Tungkal Ferry Port , there are many safety equipment that have been damaged including life jackets, lifebuoys, lifeboats and the number of safety equipment that is not in accordance with the ship's needs based on the Safety Of Life At Sea ( SOLAS). The condition and number of safety equipment must be considered both in terms of the feasibility of the equipment and the completeness of the equipment so that in the event of an emergency the existing safety equipment can be used properly as a form of implementing aspects of passenger safety on board. The number and condition of safety equipment that is not in accordance with the needs can endanger the safety of the lives of passengers in the event of an accident. The number of safety equipment must be able to accommodate the number of passengers and crew on board. Author tries to analyze the problem so that conclusions can be drawn which can later be used as solutions or problem solving suggestions that can be proposed by the author in an effort to improve supervision of the condition and number of passenger safety equipment at KMP. Satria Pratama.